Co-culture of rice and aquatic animals: An integrated system to achieve production and environmental sustainability. (10th March 2020) - Bashir, Muhammad Amjad; Liu, Jian; Geng, Yucong; Wang, Hongyuan; Pan, Junting; Zhang, Dan; Rehim, Abdur; Aon, Muhammad; Liu, Hongbin
Abstract: Rice ( Oryza sativa L.) is a staple food for three billion people and paddy fields contribute greatly to greenhouse gases (GHG) emission and environmental nitrogen losses. Rice paddies need to be managed in a novel and sustainable way to promote production. Here, we critically review the potential benefits and constrains of a novel rice production system, the co-culture of rice and aquatic animals. The review helps to answer important questions: how would the co-culture affect farm profitability, water quality, and GHG emission? What are the major benefits and constraints for adopting the co-culture system? The review revealed that rice-animal co-culture provided ecological, economic, and social benefits such as increasing farm productivity and greater resource utilization efficiencies, and that the system could increase biodiversity, improve water and soil quality, and reduce GHG emissions. However, despite its potential benefits, the adoption of the system has been constrained by the lack of science-based extension programs and the farmers' concerns over drought-related production risks. Moreover, misusing the system by adopting unpractically high culture density (high animal feed input) and/or in undesirable field conditions may lead to deteriorating water quality and lowering farm profitability. The review suggests that more research is needed to evaluate the impacts of the rice-animal co-culture system under variable climate and field conditions and to identify factors controlling their negative impacts. Furthermore, a strong extension program, with policy and technological guidance from the government and non-governmental organizations, is needed to achieve the wide adoption of the co-culture practice. Highlights: Rice-monoculture is major cause for agricultural non-point source pollution i.e. GHG emission and Nitrogen losses. Rice-animal co-culture system improves farm productivity, income, and utilization of land and water resources. Co-culture system requires maintained suitable stocking density of aquatic animals. Field management, animal escape loss, and less technical knowledge are major constraints in adoption of co-culture system.